Does stock market performance affect the government satisfaction rating in the UK? - Sen, Sedef; Donduran, Murat (PHYSICA-VERLAG GMBH & CO, 2017)
In this study, we attempt to answer the question of whether stock market performance affects the government satisfaction rating in the long run in a sample period spanning 1984:Q1 to 2013:Q2 in the UK. We examine both the equilibrium relationship and the causality relationship between stock market performance and government satisfaction rating. The results indicate that the voters are sensitive to the economic shocks and hold responsible for the government. The empirical results confirm the responsibility hypothesis.
Keywords: Stock market; Government satisfaction rating; Co-integration and asymmetric causality; US PRESIDENTIAL APPROVAL; ECONOMIC-DETERMINANTS; COINTEGRATION; POPULARITY; REGRESSIONS; HYPOTHESIS; INFERENCE; BEHAVIOR; MODELS; TESTS; Business & Economics; Mathematical Methods In Social Sciences